Answer:
4
Explanation:
Let the function given be f(x) = x³
The formula for calculating the average rate of change is expressed by:
f'(x) =
![(f(x+h)-f(x))/(h)](https://img.qammunity.org/2021/formulas/mathematics/high-school/l4avwbggink0hal6ppriwpv4iagibqcidg.png)
If f(x) = x³
f(x+h) = (x=h)³
substitute the functions in the formula
![f'(x) = ((x+h)^3-x^3)/(h)\\f'(x) = ((x^3+3xh^2+3hx^2+h^3)-x^3)/(h)\\f'(x) = (3xh^2+3hx^2+h^3)/(h)\\f'(x) = (h(3xh+3x^2+h^2))/(h)\\f'(x) = 3xh+3x^2+h^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/km2mdukex08ai5w31f929c9uhz7vm3je2v.png)
Since h = x₂-x₁ and x = 0
![f'(x) = 3(0)(2-0)+3(0)^2+(2-0)^2\\f'(x) = 0+0+2^2\\f'(x) = 4\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/3gv6rv6e5ccdx75r12sfo7ytgph4krebn2.png)
Hence the average rate of change is 4